(untitled) (Jahangirnagar University Journal of Biological Sciences, 2023)
Enteric fever or typhoid is caused by the human-specific gram-negative pathogen Salmonella enterica serovar typhi (S. typhi). The incidence of typhoid fever remains high in rural areas and the emergence of multidrug resistance has exacerbated the situation. The present study examined the antimicrobial susceptibility patterns of Salmonella typhi to the antibiotics commonly used in Bangladesh. This study also examined the status of prescription antibiotic use. From July 2016 to June 2017, a total of 40 bacterial pathogens were isolated from blood samples from 100 clinically suspected patients at a teaching hospital in Savar, Dhaka. The blood samples were subjected to analysis byWidal test, microscopy, culture and susceptibility testing using conventional bacteriological methods. A total of 40% of cases had an established bacterial etiology with S. typhi. The highest antimicrobial susceptibility to S. typhi was observed for meropenem (77.5%), gentamicin and imipenem (72.5%), and cefotaxime (70%), respectively. The maximum resistance was observed in the penicillin group, such as (80%) followed by cotrimoxazole (75%). Carbapenem-type beta-lactam antibiotics (meropenem, imipenem) and third-generation cephalosporins (cefotaxime, ceftriaxone, and ceftazidime) were the most effective drugs for typhoid fever. Prescription survey results in four cities in Bangladesh showed that typhoid patients were mainly prescribed third-generation cephalosporins such as cefixime (36.73%) and ceftriaxone (18.37%). The findings are important for an adequate identification of the pathogens and their antibiotic resistance for the correct selection of antibiotics in typhoid fever. The study has implications for the development of guidelines for prescribing antibiotics for typhoid fever in Bangladesh. Jahangirnagar University J. Biol. Sci. 11(1 & 2): 69-79, 2022 (June & December)